2019
DOI: 10.1002/er.4581
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐rich syngas production from chemical looping steam reforming of bio‐oil model compound: Effect of bimetal on LaNi 0.8 M 0.2 O 3 (M = Fe, Co, Cu, and Mn)

Abstract: Summary Chemical looping steam reforming (CLSR) of acetic acid as bio‐oil model compound is a suitable way to produce hydrogen‐rich syngas. The LaNiO3 and LaNi0.8M0.2O3 (M = Fe, Co, Mn, and Cu) perovskites were prepared via the sol‐gel method. The perovskites were characterized by X‐ray diffraction (XRD), thermogravimetry (TG), and test activity of hydrogen‐rich syngas in a fixed bed. XRD and TG results showed that the coke generation on LaNi0.8Fe0.2O3 needs a lower decomposition temperature, and a stable stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…[172] For LaNi x Fe 1-x O 3 perovskite oxygen carriers, tuning the Fe to Ni could result in optimal CLBP performance over repeated redox cycles. [177,178] When using perovskite OCs, special attentions must be paid to the reversibility of phase changes over long-term redox cycling. For example, deep reduction of CaMnO 3 could result in the irreversible accumulation of CaMn 2 O 4 , which is less reactive than CaMnO 3 .…”
Section: Mixed Oxidesmentioning
confidence: 99%
“…[172] For LaNi x Fe 1-x O 3 perovskite oxygen carriers, tuning the Fe to Ni could result in optimal CLBP performance over repeated redox cycles. [177,178] When using perovskite OCs, special attentions must be paid to the reversibility of phase changes over long-term redox cycling. For example, deep reduction of CaMnO 3 could result in the irreversible accumulation of CaMn 2 O 4 , which is less reactive than CaMnO 3 .…”
Section: Mixed Oxidesmentioning
confidence: 99%
“…Density Functional Theory calculation showed that the existence of oxygen vacancies made the diffusion barrier of O ions in Fe 2 O 3 /Fe system smaller than that of Fe cations, 32 which provided a theoretical basis for suppressing the phase segregation of NiFe 2 O 4 -based oxygen carriers by controlling the concentration of oxygen vacancies via cation doping. Consequently, promoting the formation of oxygen vacancies in NiFe 2 O 4 -based oxygen carriers can effectively improve the diffusion rate of O ions, 33,34 and then inhibit the phase segregation of NiFe 2 O 4 -based oxygen carriers. In addition, the construction of appropriate pore structure is another important way to improve the diffusion rate of O ions for NiFe 2 O 4 -based oxygen carriers.…”
Section: Mechanism Insightsmentioning
confidence: 99%
“…Until now, many previous studies put forward that catalytic steam reforming of tar or tar model compounds is considered to be one of the acceptable development trends . A variety of catalysts have been studied to realize tar removal and H 2 production during the reaction of tar steam reforming, such as catalysts with active metals (Ni, Co, Fe) and supports (Al 2 O 3, SiO 2, olivine). Among these catalysts, nickel has been widely employed as active metal for tar removal due to its economic feasibility and high activity for aromatic hydrocarbons destruction .…”
Section: Introductionmentioning
confidence: 99%